2014
DOI: 10.4269/ajtmh.13-0641
|View full text |Cite
|
Sign up to set email alerts
|

Integrated School-Based Surveillance for Soil-Transmitted Helminth Infections and Lymphatic Filariasis in Gampaha District, Sri Lanka

Abstract: Abstract. We explored the practicality of integrating surveillance for soil-transmitted helminthiasis (STH, assessed by Kato-Katz) with transmission assessment surveys for lymphatic filariasis (LF) in two evaluation units (EUs) in Gampaha district, Sri Lanka (population 2.3 million). The surveys were performed 6 years after five annual rounds of mass drug administration with diethylcarbamazine and albendazole. Each transmission assessment survey tested children (N = 1,462 inland EU; 1,642 coastal EU) sampled f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
2
22
0
Order By: Relevance
“…A national survey done about 15 years ago (2002)(2003) reported that only 6.9% of children has geohelminths with very low prevalence of all three species (roundworm-2.8%, whipworm-4.0% and hookworm-1.2%) 9 . These low figures were confirmed by subsequent studies which identified regional variations with low-and high-prevalence areas [10][11][12] . A study done in 2012 reported an extremely low prevalence (1.8%) of all geohelminths 10 in the Gampaha district (a semi-urban district of Sri Lanka) and similar low rates (roundworm-2%, whipworm-0.7% and hookworm-5%) were reported in rural areas of Sri Lanka 11 .…”
Section: Epidemiological Changes Of Helminth Infections In Sri Lankasupporting
confidence: 59%
See 1 more Smart Citation
“…A national survey done about 15 years ago (2002)(2003) reported that only 6.9% of children has geohelminths with very low prevalence of all three species (roundworm-2.8%, whipworm-4.0% and hookworm-1.2%) 9 . These low figures were confirmed by subsequent studies which identified regional variations with low-and high-prevalence areas [10][11][12] . A study done in 2012 reported an extremely low prevalence (1.8%) of all geohelminths 10 in the Gampaha district (a semi-urban district of Sri Lanka) and similar low rates (roundworm-2%, whipworm-0.7% and hookworm-5%) were reported in rural areas of Sri Lanka 11 .…”
Section: Epidemiological Changes Of Helminth Infections In Sri Lankasupporting
confidence: 59%
“…These low figures were confirmed by subsequent studies which identified regional variations with low-and high-prevalence areas [10][11][12] . A study done in 2012 reported an extremely low prevalence (1.8%) of all geohelminths 10 in the Gampaha district (a semi-urban district of Sri Lanka) and similar low rates (roundworm-2%, whipworm-0.7% and hookworm-5%) were reported in rural areas of Sri Lanka 11 . In contrast, a study done in 2009 in the plantation sector spreading across Nuwara-Eliya, Badulla, Kegalle, Ratnapura and Kandy districts reported the prevalence of geo-helminths as 29% (roundworm-24%, whipworm-6% and hookworm-5%).…”
Section: Epidemiological Changes Of Helminth Infections In Sri Lankasupporting
confidence: 59%
“…As albendazole is effective against both LF and STH it has recently been proposed to integrate STH surveillance into the TAS to evaluate the impact of LF programs on STH, and thus guide the transition from community-based deworming for LF control to school-based deworming for STH control 6. Integrated assessment of STH within a TAS has to date been piloted in Benin, Tonga,7 and Sri Lanka 8…”
Section: Introductionmentioning
confidence: 99%
“…WHO has published a protocol to help countries integrate STH data collection in TAS [13]. Two studies conducted in Sri Lanka and Burkina Faso on assessment of STH morbidity and prevalence during LF TAS enabled these countries to review their STH control strategies leading up to 2020 [14, 15]. STH data collected during TAS showed that in Burkina Faso SAC do not need deworming in area where LF MDA stopped; the STH prevalence and intensity had dropped significantly and the country is planning to review its strategy to consolidate these gains.…”
Section: Discussionmentioning
confidence: 99%